2017
DOI: 10.1097/md.0000000000008242
|View full text |Cite
|
Sign up to set email alerts
|

The current status of treatment for colorectal cancer in China

Abstract: Background:Colorectal cancer (CRC) is one of the most common cancers all over the world, but its epidemiology is obviously different in various regions.Methods:The treatment of CRC also has varying characteristics due to differences in economy, geography, disease onset, chemotherapy, and other factors, although international guidelines are used to guide the treatment of CRC in China.Results:This paper summarizes the current status of CRC treatment, including surgical therapy, neoadjuvant radiotherapy and chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
100
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(103 citation statements)
references
References 61 publications
(69 reference statements)
1
100
0
2
Order By: Relevance
“…Moreover, the current study found that a small proportion of patients treated with FOLFOX in the first-line setting either shifted to capecitabine/S1 or continued to use FOLFOX in the second-line setting, which was controversial to the guidelines for standard of care [37]. This gap between clinical practice and guidelines may be due to patients' preference, economic status, physicians' decisions [37][38][39]. Implementing education program and providing training courses to physicians as well as raising the public awareness of CRC might help with the treatment decisionmaking.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Moreover, the current study found that a small proportion of patients treated with FOLFOX in the first-line setting either shifted to capecitabine/S1 or continued to use FOLFOX in the second-line setting, which was controversial to the guidelines for standard of care [37]. This gap between clinical practice and guidelines may be due to patients' preference, economic status, physicians' decisions [37][38][39]. Implementing education program and providing training courses to physicians as well as raising the public awareness of CRC might help with the treatment decisionmaking.…”
Section: Discussionmentioning
confidence: 71%
“…This may imply poor treatment outcomes of targeted therapy in late lines, and a lack of consensus on both the timing and options for third-line treatment during the study period (2011)(2012)(2013)(2014)(2015)(2016). Moreover, the current study found that a small proportion of patients treated with FOLFOX in the first-line setting either shifted to capecitabine/S1 or continued to use FOLFOX in the second-line setting, which was controversial to the guidelines for standard of care [37]. This gap between clinical practice and guidelines may be due to patients' preference, economic status, physicians' decisions [37][38][39].…”
Section: Discussionmentioning
confidence: 74%
“…Colorectal cancer is the third leading cause of cancer-associated mortality globally (1,2). Although the majority of patients with CRC are treated using surgery combined with chemotherapy, local recurrence and remote metastases following therapy often influence their survival rate (30). At present, there is a lack of effective biomarkers for CRC recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal carcinoma is the third most common malignant tumor worldwide, with surgical resection being the only effective treatment currently available. 1,2 Despite important advances in surgical techniques, the overall rate of complications remains high, at around 30%. 3 Postoperative complications are associated with increased treatment costs, prolonged hospital stay, delayed adjuvant chemotherapy, increased risk of recurrence, and a detrimental impact on survival.…”
Section: Introductionmentioning
confidence: 99%